2021
DOI: 10.3390/ijms22168407
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Genome-Wide Study and Expression Analysis of SWEET Gene Family: Sugar Transporter Family Contributes to Biotic and Abiotic Stimuli in Watermelon

Abstract: The SWEET (Sugars Will Eventually be Exported Transporter) proteins are a novel family of sugar transporters that play key roles in sugar efflux, signal transduction, plant growth and development, plant–pathogen interactions, and stress tolerance. In this study, 22 ClaSWEET genes were identified in Citrullus lanatus (Thunb.) through homology searches and classified into four groups by phylogenetic analysis. The genes with similar structures, conserved domains, and motifs were clustered into the same groups. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 63 publications
4
13
0
Order By: Relevance
“…Ten CsSWEETs, including CsSWEET5a , - 3a , - 9a , - 7b , - 17a , - 9b , - 15c , - 10c , - 1b and - 5c , were highly expressed in one or several pollen stages of tea ( Camellia sinensis ) [ 72 ]. Most SWEET genes of watermelon showed high expression levels in male flowers [ 73 ]. During the petunia flower development, the expression level of PaSWEET13c , - 9a , - 1d , - 5a and - 14a increases with the maturation of the flower [ 74 ].…”
Section: Sweets Are Involved In Plant Growth and Developmentmentioning
confidence: 99%
“…Ten CsSWEETs, including CsSWEET5a , - 3a , - 9a , - 7b , - 17a , - 9b , - 15c , - 10c , - 1b and - 5c , were highly expressed in one or several pollen stages of tea ( Camellia sinensis ) [ 72 ]. Most SWEET genes of watermelon showed high expression levels in male flowers [ 73 ]. During the petunia flower development, the expression level of PaSWEET13c , - 9a , - 1d , - 5a and - 14a increases with the maturation of the flower [ 74 ].…”
Section: Sweets Are Involved In Plant Growth and Developmentmentioning
confidence: 99%
“…Chen and colleagues 69 identified and characterized several LEA family genes conferring tolerance to multiple environmental stresses 69 . (ii) In a recent study, Xuan and colleagues 70 reported that a higher expression level of sugar transporter genes regulates plant responses to different stresses, including drought, salt, and low-temperature stress. (iii) Transgenic plants with increased expression of the WSD1 gene, which encodes for wax synthase/acyl-CoA:diacylglycerol acyltransferase showed improved tolerance to abscisic acid, mannitol, drought, and salinity 71 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the genome-wide analysis of SWEET genes has been comprehensively conducted in several plant species, such as A. thaliana [ 9 ], rice ( Oryza sativa ) [ 13 ], lychee ( Litchi chinensis Sonn) [ 16 ], and pomegranate ( Punica granatum ) [ 17 ]. Biochemical and functional analyses have shown that SWEET genes are involved in many different functions, such as phloem loading [ 9 ], nectar secretion [ 18 ], pollen development [ 19 ], modulating gibberellins response [ 20 ], senescence [ 21 ], abiotic stress response [ 22 , 23 , 24 , 25 , 26 , 27 ], host–pathogen interactions [ 28 , 29 , 30 , 31 ], and seed and fruit development [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%